INCORPORATING HIGHER ORDER THINKING SKILLS INTO ENGLISH SUMMATIVE ASSESSMENTS - Rianti, Riska; Aziz, Zulfadli A; Aulia, Muhammad (English Review: Journal of English Education, 2024)
Higher-Order Thinking Skills (HOTS) are considered as one of the 21st-century skills in education. One of the most efficient strategies to promote HOTS is through assessment. This study aims to find out the percentage of Higher-Order Thinking Skills (HOTS) used in English teachers’ summative assessment in an Islamic junior high school in Banda Aceh. In this qualitative study, Anderson's (2001) taxonomy, which divided thinking skills into two categories: lower-order thinking skills (remembering, understanding, and applying) and higher-order thinking skills (analyzing, evaluating, creating) were applied. The object of this study was three documents of English teachers’ summative assessments containing 150 test items with 145 questions in multiple-choice form and 15 questions in essay form. The questions were listed on a checklist table and calculated into percentages that corresponded to each cognitive level. The result showed that HOTS obtained a lower distribution than LOTS in the English teachers’ summative assessments. Specifically, the percentage of HOTS was only 4.6% (7 questions) from 150 questions analyzed. In conclusion, most questions of English teachers’ summative assessment in the Islamic junior high school can be categorized mostly into Lower-Order Thinking Skills (LOTS). The findings suggest that teachers should be more conscious of HOTS implementation while creating questions. Ultimately, this will improve students’ critical and creative thinking as well as problem-solving.